Investigation of Viral Load Cycle Threshold Values in Patients with SARS-CoV-2 Associated Pneumonia with Real-Time PCR Method - Ayfer Bakir; Tugrul Hosbul; Ferhat Cuce; Cumhur Artuk; Gurhan Taskin; Murat Caglayan; Mustafa Guney; Muhammed Furkan Kurkcu; Fatime Yildiz; Harun Erdal; Gul Erdem (Journal of Infection in Developing Countries)
Introduction: In this study, we aimed investigate the relationship of SARS-CoV-2 viral load cycle threshold (Ct) values with pneumonia.